Beast [videorecording (DVD)] - Frigerio, David; Crowe, Russell, 1964-; Crowe, Russell, 1964-; MacPherson, Daniel, 1980-; Hemsworth, Luke, 1980-; Foster, Bren, 1978-; Shark, Amy, 1986- (Lionsgate, 2026)
After years away from the cage, a once-feared MMA champion is pulled back in for the fight of his life when his younger brother is put in danger. Reuniting with the trainer who once made him a legend, he commits to one final showdown against the reigning title-holder - a brutal fighter determined to dismantle the ex-champ's legacy in front of the world. Pushed to his breaking point, the contender's stakes are simple: win, or lose everything he's built.